Home blood pressure monitoring detects unrevealed hypertension in women with a history of preeclampsia: Results of the BP-PRESELF study - Hella E.C. Muijsers; Pensee Wu; Olivier W.H. van der Heijden; Lia D.E. Wijnberger; Chantal van Bijsterveldt; Ciska Buijs; Jens Pagels; Peter Tönnies; Susanne Heiden; Nel Roeleveld; Angela H.E.M. Maas (Elsevier, 2022)
Objectives: The risk of cardiovascular disease more than doubles after hypertensive disorders of pregnancy. As early onset chronic hypertension contributes to cardiovascular risk, implementation of screening strategies, using home blood pressure monitoring (HBPM), may help to improve long-term cardiovascular health.We evaluated whether HBPM among women with a history of preeclampsia/HELLP syndrome is feasible for early detection and management of hypertension. Methods: The BP-PRESELF study is a multicenter randomized controlled trial. Participants were randomized to intervention group with HBPM for the duration of 1 year or the control group with 'usual care'. The primary outcome was feasibility of HBPM during 1 year of follow-up, defined as protocol adherence, protocol persistence and patient acceptance. Secondary outcomes were blood pressure levels and prevalence of hypertension. Results: We recruited 198 women with a mean age of 45 years. Protocol adherence decreased during the first 6 months, after which it stabilized. Protocol persistence remained high throughout follow-up. During the study period, 33 women (34%) in the intervention group were diagnosed with hypertension versus only 10 women (11%) in the control group, P<0.001. At 1-year follow-up, mean systolic blood pressure (SD) was 120.4 (11.6) mmHg in the intervention group versus 126.1 (14.3) mmHg in the control group, P=0.003. Mean diastolic blood pressure (SD) values were 77.1 (8.0) mmHg versus 81.7 (9.4) mmHg, P<0.001, respectively. Adjusted systolic and diastolic differences (95% confidence interval) were -6.81 (-10.17, -3.45) and -4.93 (-7.26, -2.61) mm Hg, with 80% less hypertension at 1-year follow-up in the intervention group. Conclusions: HBPM appears to be feasible for follow-up of blood pressure in women after preeclampsia/HELLP syndrome, while it detected hypertension and blood pressure levels reduced in one-third of women in this group.